THE INFLUENCE OF LEADERSHIP STYLE AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE AT PT. BUMI MEKAR HIJAU - Agussalim, Agussalim; Hamdan, Hamdan; Enika, Popya (Jurnal Manajemen, 2023)
This study examines the analysis of the effect of leadership style and organizational culture on employee performance at PT. Bumi Mekar Hijau (BMH) Ogan Komering Ilir, South Sumatra Province. The purpose of this study is to determine whether the leadership style has a partial influence on employee performance at PT BMH then to determine whether the organizational culture has a simultaneous influence on employee performance at PT BMH and to determine which is more dominant between the influence between leadership style and organizational culture on employee performance at PT BMH. The R number is obtained 0, meaning that the correlation between the leadership style and organizational culture variables is 0.816, this means that there is a strong relationship because the value is close to 1. While the results of R Square (R2), which shows the coefficient of determination. This figure will be converted to percent form which means the percentage contribution of the dependent variable. The R2 value of 0.569 means that the contribution of leadership and motivation to job satisfaction is 56.9% while the rest is influenced by other variables not included in this study.